2000
DOI: 10.4049/jimmunol.164.12.6188
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating Cell Nuclear Antigen as the Cell Cycle Sensor for an HLA-Derived Peptide Blocking T Cell Proliferation

Abstract: Synthetic peptides corresponding to structural regions of HLA molecules are novel immunosuppressive agents. A peptide corresponding to residues 65–79 of the α-chain of HLA-DQA03011 (DQ65–79) blocks cell cycle progression from early G1 to the G1 restriction point, which inhibits cyclin-dependent kinase-2 activity and phosphorylation of the retinoblastoma protein. A yeast two-hybrid screen identified proliferating cell nuclear Ag (PCNA) as a cellular ligand for this peptide, whose interaction with PCNA was furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…We assume that this is an artifact of the two-hybrid system because we previously reported that DQ 65-79 interacts with full-length PCNA in an ELISA format (10). To convincingly demonstrate a specific interaction between DQ 65-79 and full-length PCNA, coimmunoprecipitation experiments were conducted.…”
Section: Coimmunoprecipitation Of Dq 65-79 and Pcnamentioning
confidence: 99%
See 2 more Smart Citations
“…We assume that this is an artifact of the two-hybrid system because we previously reported that DQ 65-79 interacts with full-length PCNA in an ELISA format (10). To convincingly demonstrate a specific interaction between DQ 65-79 and full-length PCNA, coimmunoprecipitation experiments were conducted.…”
Section: Coimmunoprecipitation Of Dq 65-79 and Pcnamentioning
confidence: 99%
“…Substitution of each amino acid with serine indicated that residues 66, 68, 69, 71-73, and 75-79 are critical for DQ 65-79 function. A mutant peptide in which isoleucine at position 75 was changed to serine (DQ 75S) does not inhibit T cell proliferation (9,10). Murphy et al (11) reported that a similar synthetic peptide corresponding to residues 51-57 of a rat MHC class II molecule inhibited mixed lymphocyte reactions and differentiation of CTL in a dose-dependent manner and induced apoptosis (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have not yet determined whether DQ 65-79 has a similar effect on cyclin D1 transcription. We have shown that DQ 65-79 blocks cell cycle progression at the G 1 to S transition, in part by associating with proliferating cell nuclear Ag (53). In addition, DQ 65-79, through its effect on PI-3K, blocks degradation of p27, a negative regulator of cyclins (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although MHC-derived peptides typically bind within the groove of the MHC molecule, thereby influencing the immune response, studies by our group and others have shown that MHCderived peptides may also exert their effects by binding to critical cell surface proteins participating in vital TCR-MHC interaction sites and intracellular proteins involved in the processing, presentation, and responses to Ag (6,7). Boytim et al (8) demonstrated that a synthetic peptide corresponding to the ␣1 ␣ helix of DQA03011 (DQ 65-79) inhibited alloantigen-induced T cell proliferation in an allele-independent manner (8) and DQ 65-79 bound to proliferating cell nuclear Ag, preventing cell cycle progression in a manner similar to that of rapamycin (9).…”
Section: Inhibition Of the Alloimmune Response Through The Generationmentioning
confidence: 99%